Archaeometrical characterization of pigments and paintings on Pre-Hispanic pottery from the regions of Fiambalá and Chaschuil (Catamarca, Argentina) - Ratto, Norma Rosa (2020)
The results of an analysis of pigments used in slips and designs deployed in ceramic assemblages recovered from archaeological sites located in different environments, expressing the socio-historical process developed in the regions of Fiambalá and Chaschuil (Catamarca, Argentina) during the last 1500 years are presented. The sample, formed by fragments of different ceramic styles and natural pigments, was analysed via Raman spectroscopy and X-ray diffraction. Results indicate the continuity in use of certain pigments (mainly hematite for red hues and Mn oxides in combination with magnetite for black paints) within the different socio-political organizations that inhabited the region from the first to the 14th centuries ce, in spite of the diverse shades of colour, which suggests an intentional search linked with their cultural conventions. For the Inca Period, this scenery of continuities in minerals employed for reds and blacks is complemented by the use of new compounds (Ti oxide, apatite and gypsum) in order to generate the ‘cream’ tones applied as slips, all of which have not been identified for previous moments.